Baltic Sea Geophysical Student Field Trip, Cruise No. AL527, 06.09.2019 – 14.09.2019 Kiel (Germany) – Kiel (Germany) - Krastel, Sebastian; Berndt, Christian; Schneider von Deimling, Jens; Lenz, Kai Frederik; Held, Philipp; Kühn, Michael; Nielsson, Per Oscar; Hans, Anna Christina; Weiler, Tatjana Michaela; Liebsch, Jonas; Prigan, Theresa; May, Tilman; et al. (Christian-Albrechts-Universität zu Kiel, 2019)
The cruise AL527 took place in the Western Baltic Sea in the period 6. – 14.09.2019. The cruise was carried out as a marine geophysical field course of Kiel University, supported by BONUS ECOMAP project. Starting and ending point of the cruise was Kiel. One stopover in Kiel took place during the cruise due to an exchange of parts of the scientific party (10.09.2019). The main aim of the cruise was to introduce marine geophysical acquisition to the students including hands-on experience in collecting marine geophysical data. This approach also included a first processing and interpretation of the data as well as the presentation of the first results. Two areas in the Western Baltic Sea were the main working areas of AL527. The first survey area was at Boknis Eck, a part of the Eckernförde Bay. The main objective in this area was to search for an underwater observatory from the Coastal Observing System for Northern and Arctic Seas Project (COSYNA), which was operated by GEOMAR and disappeared end of August 2019. For this purpose, a survey with a bathymetric multibeam system from the ”Marine Geophysics and Hydroacoustics” working group (Kiel University) was carried out. Furthermore, an underwater camera system was used for visual inspections. The second survey area was in the Mecklenburger Bay. The main objective was a pre-investigation of a buried beach for an upcoming cruise within the EU-funded project ACT-SENSE. Therefore, 2D reflections seismic, sediment echo sounder, and multibeam data were acquired. Additionally, 7 gravity cores were taken for ground trothing and sampling of the buried beach. In order to analyze major tectonic structures in the Fehmarn Belt and the Mecklenburger Bay, 12 additional seismic profiles were collected when transiting between the survey areas. Our investigations showed that a buried beach is located in the Mecklenburger Bay beneath a layer of mud. The sand deposits have an estimated variable thickness between 1m and 9m in the survey area. The top of the beach was successfully ...